The ACCEPTANCE AND SAVING LIFE ESTIMATION OF BMC (MIXED FOOD INGREDIENTS) VARIANTS OF BISCUIT SUBSTITUTED IN FISH FLOUR AND KELOR (Moringa oleifera) BASED LOCAL FOOD DRY LAND FOR TODDLER IN KUPANG DISTRICT - Indriati Andolita Tedju Hinga (CHMK Applied Science Journal, 2021)
Inadequate nutritional intake both in terms of quality and quantity is one of the causes of nutritional problems that occur in children, especially toddlers. Nutrition-dense supplementary food (PMT) is one solution to improve the recovery of malnutrition problems. Mixed food ingredients in the form of biscuits substituted for fish meal and Moringa oleifera or TIK are an innovative product as PMT. TIK biscuits are nutritional supplements based on local food potential in dry land areas. TIK biscuits are processed into 4 (four) flavor variants, namely chocolate, vanilla, vanilla bean and palm nut flavors. These biscuits are highly recommended to maintain and improve the nutritional status of toddlers with normal weight and low body weight in order to prevent cases of malnutrition and malnutrition and stunting in toddlers. This research method used experiment design with 25 panelists. Based on the hedonic test which includes color, taste, texture and aroma. The recommendation for the TIK biscuit products that the children liked the most in terms of color, taste and texture were the TIK chocolate biscuits, while in terms of aroma were the TIK vanilla snack and vanilla beans. Overall, the variations of the TIK chocolate, vanilla and vanilla bean snacks were preferred by children compared to the palm nut variants, but the palm nut variants were preferred by adults. All variations of TIK snack products, namely chocolate, vanilla beans, vanilla and palm nuts have a good and long lasting storage period so that they can be made in large quantities as PMT to increase the daily nutritional intake of toddlers in order to achieve optimal growth and development. Keywords: Biscuits, Fish Flour, Moringa, Toddler